Penerapan Model Pembelajaran Discovery Learning Berbantuan Moodle untuk Meningkatkan Keterampilan Berfikir Kritis Siswa - Muhammad Imam Badruttamam; Neng Rodiah Pertiwi (Pedagogi: Jurnal Ilmu Pendidikan, 2023)
Global challenges and competition require quality human resources to compete in society with 21st-century skills. Critical thinking skills are competencies to be able to solve problems needed to answer a challenge in the present as well as challenges in the future. The application of learning models is very influential in triggering critical thinking, one of which is the discovery learning model. The discovery learning model assisted by the Moodle platform helps students get the distribution of the material being taught. The purpose of this study was to analyze students' critical thinking skills by applying the Moodle-assisted discovery learning model in the biology learning activities of the immune system. This research is a quantitative research using a quasi-experimental method. The results of the N-Gain test get the N-Gain value of the experimental class more significant than the control class. Students' critical thinking skills are significant before and after using the Moodle-assisted discovery learning model.